POLA KOMUNIKASI SINGLE PARENT TERHADAP PERKEMBANGAN KARAKTER ANAK - Aisy, Nisrina Syifa; Purba, Veny (Jurnal Common, 2020)
The pattern of communication between single parent parents and children is very influential on the attitudes and behavior of children, but some of the parents of single parents some cases are left due to divorce or because of death. Interpersonal communication is very influential in the communication patterns of single parent parents carry out their role as parents who must provide moral and moral support for the character formation of children. This study aims to determine the effect of single parent parental communication patterns on the character formation of children. This research uses qualitative methods with case studies. Single father and single mother research subjects who were abandoned due to divorce or who were left due to death. Data collection using observation and interview methods. The results of research on the subject indicate that the pattern of communication between single parent parents and children is very important in shaping the character of children. Subjects have some obstacles in carrying out their role, and some of them have obstacles in playing the role of father / mother for children, some of them have obstacles when they have to portray the figure of a father for single parent mothers, and become a mother figure for single parent fathers The theory used for this research is role theory where single parent parents play the role of the actor who gives the message to the child as the target.